The coffee charm: understanding the relationship between product design dimensions and Willingness to buy from Starbucks - Bobby Ardiansyahmiraja; Siti Rahayu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2023)
The growth of the hospitality industry calls for further understanding. The coffee shop sector is a large part of the hospitality industry in Indonesia, considering coffee consumption, exports, and interest. This study uses PLS-SEM to assess the relationship between product design dimensions in coffee shops and the Willingness to buy using Starbucks as a case. A purposive sampling method was utilized to gather respondents that is a customers of Starbucks, and 119 respondents’ data was used to test the hypotheses in this study. This study found that symbolic design significantly affects WOM (β=0.210, p=0.030) and Willingness to buy (β=0.359, p